Stage to Studio : Musicians and the Sound Revolution, 1890-1950 - Kraft, James P. (Book collections on Project MUSE., 1996)
Combining ideas and techniques from business, labor, and social history, Kraft offers an illuminating case study in the impact of technology on industry and society. He stresses that capital and capitalism were as important in the entertainment industry as they were in steel manufacturing or coal mining. At the same time, he explains that the technological changes faced by musicians were not some anonymous force but were socially constructed. Finally, since the history of musicians represents part of cultural history, Kraft suggests that changes in the lives of musicians reflected and related to cultural changes as well as to organizational and technological ones.